Integrating Indonesian Realistic Mathematics Education (PMRI) and STEM Approaches in High School Students: A Systematic Literature Review - Novi Susanti; Ratu Ilma Indra Putri; Nyimas Aisyah; Hartono Hartono (Indiktika : Jurnal Inovasi Pendidikan Matematika, 2025)
This study presents a Systematic Literature Review (SLR) on the integration of the Indonesian Realistic Mathematics Education (PMRI) and STEM approaches in mathematics learning. The review aims to map research trends, learning contexts, mathematical content, developed competencies, and key findings of studies published between 2015 and 2025. The review process involved identification, screening based on explicit inclusion and exclusion criteria, and thematic synthesis of articles obtained from reputable academic databases. Out of all identified articles, 15 studies passed a rigorous selection process and were analyzed in depth. The findings indicate that PMRI–STEM integration is commonly implemented through real-world contextual problems combined with investigative activities, mathematical modeling, and design-based projects. This approach has been applied across various topics, including geometry, measurement, algebra, trigonometry, and numeracy. The reviewed studies report positive contributions to conceptual understanding, problem-solving skills, mathematical literacy, creative thinking, and other higher-order thinking skills. In addition to its impact on students, several studies also highlight improvements in teachers’ competence in designing technology-supported contextual learning. Unlike previous reviews that examined PMRI or STEM separately, this study specifically focuses on their pedagogical integration in mathematics education. The review concludes that PMRI–STEM integration holds strong potential as an innovative and interdisciplinary framework aligned with 21st-century learning demands and recommends more systematic instructional designs and broader implementation across educational levels.